2018
DOI: 10.1016/j.carj.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Based Contrast Agents in Kidney Disease: Comprehensive Review and Clinical Practice Guideline Issued by the Canadian Association of Radiologists

Abstract: Use of gadolinium-based contrast agents (GBCAs) in renal impairment is controversial, with physician and patient apprehension in acute kidney injury (AKI), chronic kidney disease (CKD), and dialysis because of concerns regarding nephrogenic systemic fibrosis (NSF). The position that GBCAs are absolutely contraindicated in AKI, CKD stage 4 or 5 (estimated glomerular filtration rate [eGFR] <30 mL/min/1.73 m) and dialysis-dependent patients is outdated, and may limit access to clinically necessary contrast-enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 110 publications
(186 reference statements)
0
62
0
1
Order By: Relevance
“…For the general population, the best described technique is based on the delayed washin and washout of the contrast agent from the tissues with increased extracellular space—late gadolinium enhancement (LGE). In advanced CKD, the usage of gadolinium based contrast agents (GBCA) should be considered individually as it is limited by the risk (<1%) of developing a potentially lethal condition, nephrogenic systemic fibrosis (NSF) . In the past years, it was shown that persons with normal renal function can also develop NSF when exposed to GBCA, but until the exact pathophysiology of GBCA‐induced disease is better understood, alternative gadolinium‐free methods should be used whenever possible in advanced CKD …”
Section: Cardiac Magnetic Resonance (Cmr)mentioning
confidence: 83%
See 2 more Smart Citations
“…For the general population, the best described technique is based on the delayed washin and washout of the contrast agent from the tissues with increased extracellular space—late gadolinium enhancement (LGE). In advanced CKD, the usage of gadolinium based contrast agents (GBCA) should be considered individually as it is limited by the risk (<1%) of developing a potentially lethal condition, nephrogenic systemic fibrosis (NSF) . In the past years, it was shown that persons with normal renal function can also develop NSF when exposed to GBCA, but until the exact pathophysiology of GBCA‐induced disease is better understood, alternative gadolinium‐free methods should be used whenever possible in advanced CKD …”
Section: Cardiac Magnetic Resonance (Cmr)mentioning
confidence: 83%
“…In advanced CKD, the usage of gadolinium based contrast agents (GBCA) should be considered individually as it is limited by the risk (<1%) of developing a potentially lethal condition, nephrogenic systemic fibrosis (NSF). 86,87 In the past years, it was shown that persons with normal renal function can also develop NSF when exposed to GBCA, but until the exact pathophysiology of GBCA-induced disease is better understood, alternative gadolinium-free methods should be used whenever possible in advanced CKD. 87,88 Native T1 is a novel noncontrast CMR technique based on the longitudinal recovery time of hydrogen atoms following their excitation.…”
Section: Ard Iac Mag Ne Ti C Re Sonan Ce (Cmr )mentioning
confidence: 99%
See 1 more Smart Citation
“…This life‐threatening condition is characterized by extensive fibrosis of the skin and internal organs, with delay from exposure to onset of the first signs ranging from the day of exposure to 2–3 months . To date, several hundred cases have been diagnosed worldwide and data over subsequent years indicated that NSF is strongly associated with the administration of GBCAs in patients with severe renal impairment or on dialysis . The use of less stable linear GBCAs is another major risk factor due to their higher propensity to release free gadolinium .…”
mentioning
confidence: 99%
“…6 To date, several hundred cases have been diagnosed worldwide and data over subsequent years indicated that NSF is strongly associated with the administration of GBCAs in patients with severe renal impairment or on dialysis. 7 The use of less stable linear GBCAs is another major risk factor due to their higher propensity to release free gadolinium. 5,8 Gadolinium deposits were found in cutaneous biopsies of patients 9 but the exact mechanism by which gadolinium triggers NSF is still incompletely understood.…”
mentioning
confidence: 99%